Kininogen deficiency protects from ischemic neurodegeneration in mice by reducing thrombosis, blood-brain barrier damage, and inflammation - Langhauser, Friederike; Pham, Mirko; Bendszus, Martin (Blood, 2012)
Thrombosis and inflammation are hallmarks of ischemic stroke still unamenable to therapeutic interventions. High-molecular-weight kininogen (KNG) is a central constituent of the contact-kinin system which represents an interface between thrombotic and inflammatory circuits and is critically involved in stroke development. Kng−/− mice are protected from thrombosis after artificial vessel wall injury and lack the proinflammatory mediator bradykinin. We investigated the consequences of KNG deficiency in models of ischemic stroke. Kng−/− mice of either sex subjected to transient middle cerebral artery occlusion developed dramatically smaller brain infarctions and less severe neurologic deficits without an increase in infarct-associated hemorrhage. This protective effect was preserved at later stages of infarction as well as in elderly mice. Targeting KNG reduced thrombus formation in ischemic vessels and improved cerebral blood flow, and reconstitution of KNG-deficient mice with human KNG or bradykinin restored clot deposition and infarct susceptibility. Moreover, mice deficient in KNG showed less severe blood-brain barrier damage and edema formation, and the local inflammatory response was reduced compared with controls. Because KNG appears to be instrumental in pathologic thrombus formation and inflammation but dispensable for hemostasis, KNG inhibition may offer a selective and safe strategy for combating stroke and other thromboembolic diseases.
Gesehen am 01.10.2018